2017
DOI: 10.1038/srep41360
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between bony tunnel and knee function in patients after patellar dislocation triple surgeries—a CT-based study

Abstract: We aimed to assess the CT-based bony tunnel valuations and their correlation with knee function after patellar dislocation triple surgeries. A retrospective study was performed on 66 patients (70 knees) who underwent patellar dislocation triple surgeries. The surgery was MPFL reconstruction primarily, combined with lateral retinaculum release and tibial tubercle osteotomy. CT examinations were performed to determine the femoral tunnel position, along with the patellar and femoral tunnel width 3 days and more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Three studies utilized bioabsorbable screws [ 10 , 17 , 18 ]. Qin et al used both titanium and bioabsorbable screws [ 19 ], whereas type of screw used was not reported in three studies [ 11 , 12 , 20 ]. Of the 365 patients identified, 212 had recurrent patellar dislocation (more than two previous episodes).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies utilized bioabsorbable screws [ 10 , 17 , 18 ]. Qin et al used both titanium and bioabsorbable screws [ 19 ], whereas type of screw used was not reported in three studies [ 11 , 12 , 20 ]. Of the 365 patients identified, 212 had recurrent patellar dislocation (more than two previous episodes).…”
Section: Resultsmentioning
confidence: 99%
“…Neri et al did not report degree of FTE [ 11 ], whereas Kita et al reported association between FTE and potential risk factors without reporting values for these [ 20 ]. The case series by Qin et al [ 19 ] and Wong et al [ 18 ] carried some concerns regarding their risk bias due to their retrospective nature and being performed in a single center. Only one non-randomised comparative study was identified [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 13 Theoretically, the abnormal TT‐TG distance of the Chinese population being shorter than the critical value reported in the literature is due to the different sizes and shapes of the bones and muscles of knee joints. Although few studies have focused on the TT‐TG distance in Chinese subjects, 14 , 15 more clinical data are needed to verify the differences in TT‐TG distance between Chinese and foreign populations due to bias and limitations in measurement methods. Furthermore, the exact mechanism of patellofemoral instability has not been clearly clarified.…”
Section: Introductionmentioning
confidence: 99%